Conservation of forest genetic resources in protected areas - National Park “Kopaonik” as an example of good practice - Nonić Marina; Šijačić-Nikolić Mirjana; Vilotić Dragica (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2023)
Protected areas represent an important form of in situ conservation and sustainable use of forest genetic resources. Compared to other forest complexes, these areas are less threatened, but they are also exposed to threatening factors that lead to genetic erosion. Bearing in mind that the loss of genetic diversity represents one of the greatest threats to the preservation of the adaptive potential of species, important for the survival of forests in conditions of climate change, the conservation of forest genetic resources can be considered an important activity in all protected areas. In recent decades, activities on the conservation of the gene pool of forest species in protected areas in Serbia have been intensified, and concrete results are already visible in some of them. As an example of good practice, this paper presents activities on the identification of rare, endangered, relict, endemic, and vulnerable woody species in the area of the National Park “Kopaonik”, in the regime of first and second degree protection, along with an assessment of their degree of endangerment. Based on the obtained results, conservation measures of the available gene pool were proposed, the implementation of which is expected in the following period.